ERH Gene and Its Role in Cancer Cells - Pang, Kun; Li, Mei-li; Hao, Lin; Shi, Zhen-duo; Feng, Harry; Chen, Bo; Ma, Yu-yang; Xu, Hao; Pan, Deng; Chen, Zhe-Sheng; Han, Cong-hui (Frontiers in Oncology, 2022)
Cancer is a major public health problem worldwide. Studies on oncogenes and tumor-targeted therapies have become an important part of cancer treatment development. In this review, we summarize and systematically introduce the gene enhancer of rudimentary homolog (ERH), which encodes a highly conserved small molecule protein. ERH mainly exists as a protein partner in human cells. It is involved in pyrimidine metabolism and protein complexes, acts as a transcriptional repressor, and participates in cell cycle regulation. Moreover, it is involved in DNA damage repair, mRNA splicing, the process of microRNA hairpins as well as erythroid differentiation. There are many related studies on the role of ERH in cancer cells; however, there are none on tumor-targeted therapeutic drugs or related therapies based on the expression of ERH. This study will provide possible directions for oncologists to further their research studies in this field.